2014
DOI: 10.1007/s10571-014-0143-9
|View full text |Cite
|
Sign up to set email alerts
|

IL-33 Expression in the Cerebral Cortex Following Experimental Subarachnoid Hemorrhage in Rats

Abstract: Subarachnoid hemorrhage (SAH) is a pervasive and devastating condition in which inflammatory and apoptotic pathways contribute to poor outcome. Interleukin-33 (IL-33) plays a crucial role in the inflammatory and apoptotic pathways through binding of the transmembrane ST2 receptor. This study investigated the expression and cellular localization of IL-33 in the cerebral cortex after SAH in order to clarify the role of IL-33 after SAH. Sprague-Dawley rats were randomly divided into sham and SAH groups and evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Numerous literatures identified that IL-33 is dominantly produced by endothelial cells and astrocytes but not by microglia or neurons in vitro cellar culture (Manetti et al, 2010 ; Yasuoka et al, 2011 ). Other reports revealed that IL-33 was mainly localized in astrocytes, microglia and neurons after brain injury in vivo (Huang et al, 2015 ; Gao et al, 2017 ). We speculate the reason for the discrepancy may be caused by the different experiment settings, environments between in vitro and in vivo , or because of tissue repair process after acute brain injury.…”
Section: Discussionmentioning
confidence: 87%
“…Numerous literatures identified that IL-33 is dominantly produced by endothelial cells and astrocytes but not by microglia or neurons in vitro cellar culture (Manetti et al, 2010 ; Yasuoka et al, 2011 ). Other reports revealed that IL-33 was mainly localized in astrocytes, microglia and neurons after brain injury in vivo (Huang et al, 2015 ; Gao et al, 2017 ). We speculate the reason for the discrepancy may be caused by the different experiment settings, environments between in vitro and in vivo , or because of tissue repair process after acute brain injury.…”
Section: Discussionmentioning
confidence: 87%
“…Numerous literatures identified that IL-33 is produced by endothelial cells and astrocytes but not by microglia or neurons (Manetti et al, 2010 ; Yasuoka et al, 2011 ), and its receptors are mainly expressed in microglia and astrocytes in vitro cellar culture (Yasuoka et al, 2011 ). Other reports revealed that IL-33 was mainly localized in astrocytes, microglia and neurons after brain injury in vivo (Huang et al, 2015 ; Gao et al, 2017 ). Consistent with the latter, our current results showed that IL-33 almost exclusively located in the nucleus of astrocytes, and in the cytoplasm of microglia and neurons.…”
Section: Discussionmentioning
confidence: 87%
“…However, IL-33 has been assigned to play an inflammatory role in CNS reflecting its pleiotropic nature [ 110 , 112 ]. Huang, et al [ 113 ] have observed an increased expression of IL-33 mRNA and protein in the cerebral cortex of the rats after experimental SAH. Intriguingly, IL-33 expression colocalized with neuronal and astrocytic markers and mRNA expression of IL-33 correlated with that of IL-1β after SAH [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…Huang, et al [ 113 ] have observed an increased expression of IL-33 mRNA and protein in the cerebral cortex of the rats after experimental SAH. Intriguingly, IL-33 expression colocalized with neuronal and astrocytic markers and mRNA expression of IL-33 correlated with that of IL-1β after SAH [ 113 ]. So, IL-1α and IL-33 represent important DAMPs implicated in neuroinflammation after experimental SAH and therefore, needs further investigations.…”
Section: Resultsmentioning
confidence: 99%